Navigating the obesity paradox in bladder cancer prognosis—insights from the Taiwan National Health Insurance System Database - Tseng, Wen-Hsin; Chiang, Ting-Yi; Ho, Chung-Han; Huang, Steven K.; Chiu, Allen W.; Li, Chien-Feng; Shiue, Yow-Ling (Frontiers in Nutrition, 2024)
Purpose: This study investigates the complex relationship between body mass index (BMI) and bladder cancer outcomes, utilizing Taiwan's national database. Bladder cancer remains a significant health concern, especially in Taiwan, prompting a comprehensive retrospective analysis to explore the impact of obesity on survival outcomes. Materials and Methods: A meticulous exclusion process, based on Taiwan National Health Insurance System Database, refined the initial dataset of 15,086 bladder cancer patients to 10,352. Categorizing patients into BMI groups (underweight, normal weight, obesity), the study examined baseline characteristics, comorbidities, and survival outcomes. The analysis involved Cox regression and subgroup assessments stratified by clinical stage. Results: Among our patients, 71.5% are male, 78.5% are over 60 years of age, and 18.8% are between 45 and 60 years old. Despite a higher prevalence of comorbidities, obesity patients exhibited a more favorable prognosis, supporting the obesity paradox. The overall and specific mortality ratio of obesity patients were 0.76 fold and 0.82-fold compared with normal-weight patients (overall: 95% confidence interval [CI], 0.71-0.82, P<0.0001; specific: 95% CI, 0.75-0.90, P<0.0001). Conversely, underweight patients displayed an increased risk of both overall and cancer-specific mortality compared to normal-weight patients (p<0.0001). Conclusion: This study highlights the potential protective role of higher BMI in bladder cancer survival, revealing a more favorable prognosis among obesity patients, highlighting the need for cautious interpretation and suggesting avenues for future research. These insights could guide BMI-targeted intervention strategies, allowing clinicians to consider BMI as a factor in personalized treatment planning for bladder cancer patients.